(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Tracheostomy is a surgical intervention that establishes an airway via creation of an opening into trachea. It is indicated in case of upper airway obstruction, secretions management, prolonged mechanical ventilation, and for the purpose of performing other interventions. It is necessary to provide postoperative care in order to avoid complications like bleeding, obstruction, infection, and tracheal stenosis. Materials and Methods: It is a hospital based observational study that involves 90 patients, admitted at Assam Medical College & Hospital, Dibrugarh, in Department of Otorhinolaryngology suffering from respiratory problems or head-neck trauma and patients admitted in other departments needing tracheostomy. Results: From the total number of 90 patients, majority were males (87.77%) with a mean age of 50±17.18 years. 70% of them undergone emergency tracheostomy due to difficulty in breathing, whereas 30% had elective tracheostomies. Upper airway obstruction was the main cause (62.23%), followed by prolonged ventilation in ICU patients (22.22%). This study found out that there are some differences regarding the anatomical site involved and some possible complications like bleeding, respiratory problems, and infections at the tracheostomy stoma site. Conclusion: In summary, this study highlights the necessity for further development of tracheostomy through evidence-based practice and research for exceptional patient care.